Prostate-specific membrane antigen PET versus [99mTc]Tc-MDP bone scan for diagnosing bone metastasis in prostate cancer: a head-to-head comparative meta-analysis - Wang, Yiming; Qiu, Yiran; Yan, Xingjian (Frontiers in Medicine, 2024)
Purpose: To evaluate the diagnostic performance of PSMA PET/CT, including [ 68 Ga]Ga-PSMA-11 and [ 18 F]DCFPyL, in comparison with the [ 99m Tc]Tc-MDP bone scan(BS) in identifying bone metastases among prostate cancer patients. Methods: A search was performed in the PubMed and Embase databases to locate pertinent publications from inception to February 12, 2024. The studies included were those that examined the diagnostic effectiveness of PSMA PET/CT (covering [ 68 Ga]Ga-PSMA-11 and [ 18 F]DCFPyL) compared to [ 99m Tc]Tc-MDP BS in identifying bone metastases among prostate cancer patients.The quality of the selected studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) checklist.The meta-analysis included nine articles involving 702 patients. The sensitivity of PSMA PET/CT was higher compared to [ 99m Tc]Tc-MDP BS (0.98 vs. 0.85, P<0.01), while the specificity of PSMA PET/CT was also higher than [ 99m Tc]Tc-MDP BS (0.97 vs. 0.70,P<0.01).In subgroup analysis, the sensitivity of [ 68 Ga]Ga-PSMA-11 PET/CT was higher compared to [ 99m Tc]Tc-MDP BS (0.98 vs. 0.86), while the specificity of [ 68 Ga]Ga-PSMA-11 PET/CT was also higher than [ 99m Tc]Tc-MDP BS (0.98 vs. 0.65).Our meta-analysis demonstrates that PSMA PET/CT exhibits superior sensitivity and specificity in comparison with [ 99m Tc]Tc-MDP BS for identifying bone metastases in prostate cancer patients. Further research with head-to-head design is necessary to validate these results and evaluate the clinical effectiveness of these imaging methods.